Machiavellianism dimensions, religiosity, social environment, and tax evasion - Jean Stevany Matitaputty; Priyo Hari Adi (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This research aims to investigate the effects of Machiavellianism dimensions that consist of the use of manipulative tactics, cynical views, and disregard of conventional morality on tax evasion. Further, we also analyze the effects of religiosity and social environment as the variables that control Machiavellianism behavior. The population in this research are individual taxpayers, and the sampling technique used is an online survey with the snowball sampling method. The criteria used in sampling are taxpayers who are self-employed or entrepreneurs. The data is then analyzed using the univariate and multivariate General Linear Model (GLM) methods. The results show that manipulative tactics and disregard of conventional morality have positive effects on tax evasion. Meanwhile, cynical views have a negative effect on tax evasion. Further, religiosity has negative effects on the use of manipulative tactics and disregard of conventional morality. Lastly, social environment has a positive effect on cynical views but no significant effects on the use of manipulative tactics and disregard of conventional morality.